From Harvest to Hedonism: Fear of Missing Out (FOMO), Conformity, and Consumptive Behavior Among Oil Palm Farmers in Rokan Hilir Regency from an Islamic Economic Perspective - Indra Indra; Oman Sukmana; Tri Sulistyaningsih; Junaidi Junaidi (Sharia Economic and Management Business Journal (SEMBJ), 2026)
Background: The rising income of smallholder oil palm farmers in Rokan Hilir Regency, Riau Province, Indonesia, has paradoxically fuelled consumptive spending patterns that prioritise symbolic goods over productive investment. Drawing on Jean Baudrillard's theory of consumer society and sign value, this study investigates how Fear of Missing Out (FOMO), conformity, celebrity endorsement, and self-esteem collectively drive consumptive behaviour among oil palm farmers, and how these dynamics are mediated through an Islamic economic lens. Method: This study adopts a qualitative case-study design with an interpretive paradigm. Data were gathered through in-depth interviews with ten smallholder oil palm farmers in Rokan Hilir, supplemented by interviews with seven key informants comprising village heads, local government officials, and banking representatives. Long-term observational fieldwork and documentary analysis were also employed to triangulate findings. Thematic and interpretive analysis guided data interpretation. Results: Four key findings emerge: (1) FOMO functions as a primary psychological trigger that transforms social anxiety into impulsive purchasing; (2) conformity operates as a social mechanism reinforcing status-oriented consumption; (3) celebrity endorsement through social media accelerates aspirational spending by constructing a hyperreal vision of prosperity; and (4) low self-esteem causes farmers to compensate through conspicuous goods. The study reveals that oil palm farmers consume not merely to meet needs but to perform social identity and simulate economic success, consistent with Baudrillard's simulacra framework. Conclusion: Consumptive behaviour among oil palm farmers is a structurally embedded social practice shaped by symbolic competition, income volatility, and digital media penetration. From an Islamic economic perspective, this pattern violates the principles of israf (wastefulness) and infaq fi sabilillah (purposeful spending). Interventions through financial literacy, Sharia-based financial planning, and community-level moral economy education are recommended to redirect agrarian income toward long-term productive investment.